Answer :

Let the first term be a and the common ratio be r.


According to the question,


ap+q = m.


ap-q = n.


an = arn-1


ap+q = a.rp+q-1


ap-q = a.rp-q-1


a.rp+q-1 = m.


a.rp-q-1 = n.


Multiplying above two equations we get


a2r(p+q-1+(p-q-1) = a2r(2p-2)


a2r(2p-2) = m.n


(ar)2(p-1) = m.n


arp-1 =√m.n


Pth term is given by a.rp-1


arp-1 =√m.n


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

The product of thRD Sharma - Mathematics

Express <imRS Aggarwal - Mathematics

If a, b, c are inRS Aggarwal - Mathematics

Express <imRS Aggarwal - Mathematics

Prove that RS Aggarwal - Mathematics

If a, b, c are inRS Aggarwal - Mathematics

The sum of n termRS Aggarwal - Mathematics

If a, b, c, d areRS Aggarwal - Mathematics

Evaluate :
</p
RS Aggarwal - Mathematics

The first term ofRS Aggarwal - Mathematics